Blockchain-based computing and wireless communication resource joint management double auction model - Yan SUN; Ao XIONG; Chengling JIANG; Wei WANG; Dongxiao YU; Shaoyong GUO (Tongxin xuebao)
In wireless communication networks, the stock of spectrum, computing, storage and other resources at the edge was limited.The traditional decentralized and exclusive resource allocation resulted in weak resource reuse capability and low utilization rate.At the same time, it was difficult to ensure the fairness of resource sharing in the traditional resource scheduling process due to the lack of trust between the owners.First, a double auction model of computing and wireless communication resource joint management based on blockchain was proposed.In the model, a resource market was established, in which resource buyers and sellers allocated resources through double auctions.Secondly, blockchain was used to store the resource information of buyers and sellers to solve the mutual trust problem of all parties in the network.Finally, the experimental simulation was carried out to verify that the proposed model effectively improved the system performance and resource utilization efficiency.